2010
DOI: 10.1039/c0cc02394a
|View full text |Cite
|
Sign up to set email alerts
|

Guest-induced capsule formation based on concerted interactions in water at neutral pH

Abstract: The interaction of a tetracationic calixarene (TAC4) with dianionic guest (BS) in water was studied with NMR, nano-ITC and ESI-MS experiments; the convergent evidence provided by these different techniques shows that the addition of a suitable guest molecule triggers the formation of a homodimeric capsule in aqueous neutral solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 29 publications
(20 reference statements)
1
26
0
Order By: Relevance
“…To further corroborate the complex species formation depicted by electronic absorption and 1 H‐NMR spectroscopy, we resorted to diffusion‐ordered NMR spectroscopy (2 D DOSY) experiments, because this technique allows the determination of the size of large supramolecular aggregates or highly symmetric noncovalent structures in solution …”
Section: Resultsmentioning
confidence: 99%
“…To further corroborate the complex species formation depicted by electronic absorption and 1 H‐NMR spectroscopy, we resorted to diffusion‐ordered NMR spectroscopy (2 D DOSY) experiments, because this technique allows the determination of the size of large supramolecular aggregates or highly symmetric noncovalent structures in solution …”
Section: Resultsmentioning
confidence: 99%
“…Within this framework, we have recently shown that a tetracationic calix [4]arene receptor (TAC4, Scheme 1) is able to recognize organic anions with different functionalities, shapes, charge 27,28 and to form supramolecular capsules in water at physiological pH. 29 Specically designed guests, having two aromatic and negatively charged head groups (BSCn, n ¼ 2 and 6, Scheme 1), trigger the self-assembling of homodimeric capsules with TAC4 relying on concerted hydrophobic and electrostatic interactions. 30 Capsule formation in water has been undoubtedly conrmed by a host of techniques such as combined NMR, MS and ITC data.…”
Section: Introductionmentioning
confidence: 99%
“…17 Pyrogallol[4]arene hexamers were further explored for guest encapsulation using fluorescent molecular probes such as pyrene butyric acid (PBA), 18 and ADMA. 19 Likewise, dianionic guests with tetracation calix[4]arene 20,21 and C 70 with t-Bu-calix[6]arene 22 are excellent examples of host-guest complexes.In the current study, we have utilized humalog insulin as a biotemplate for resorcin[4]arene (Rs) macrocycles to investigate the possibility of panelling the macrocycles onto the insulin moiety, thereby effectively constructing larger hosts.…”
mentioning
confidence: 99%
“…17 Pyrogallol[4]arene hexamers were further explored for guest encapsulation using fluorescent molecular probes such as pyrene butyric acid (PBA), 18 and ADMA. 19 Likewise, dianionic guests with tetracation calix[4]arene 20,21 and C 70 with t-Bu-calix[6]arene 22 are excellent examples of host-guest complexes.…”
mentioning
confidence: 99%
See 1 more Smart Citation